2011 IEEE Vehicular Technology Conference (VTC Fall) 2011
DOI: 10.1109/vetecf.2011.6093300
|View full text |Cite
|
Sign up to set email alerts
|

Near-Capacity Network Coding for Cooperative Multi-User Communications

Abstract: Abstract-In this contribution, we investigate Near-Capacity Multiuser Network-coding (NCMN) based systems using an Irregular Convolutional Code, a Unity-Rate Code and M-ary Phase-Shift Keying. In the NCMN based systems, we consider a multiuser network in which the users cooperatively transmit independent information to a common base station (BS). Extrinsic Information Transfer (EXIT) charts were used for designing the proposed NCMN scheme. The design principles presented in this contribution can be extended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Moreover, as seen in Fig. 5, the distance of γ = 0.5 dB from the DCMC capacity demonstrated that our 36-component-IrCC based coding arrangement outperforms the corresponding coding arrangement employing a 17-component IrCC code, which operates at a distance of γ = 1.0 dB from the corresponding DCMC capacity, as presented in [1].…”
Section: B Near-capacity Channel Code Designmentioning
confidence: 60%
See 2 more Smart Citations
“…Moreover, as seen in Fig. 5, the distance of γ = 0.5 dB from the DCMC capacity demonstrated that our 36-component-IrCC based coding arrangement outperforms the corresponding coding arrangement employing a 17-component IrCC code, which operates at a distance of γ = 1.0 dB from the corresponding DCMC capacity, as presented in [1].…”
Section: B Near-capacity Channel Code Designmentioning
confidence: 60%
“…In order to exploit the benefits of the turbo principle, an interleaver (π) is employed for efficiently spreading the extrinsic information in support of the inner iterations occurring between the intrinsically amalgamated URC-MPSK decoder and the IrCC decoder. In contrast to the IrCC-URC-MPSK scheme of [1] employing a 17-component IrCC code, a more powerful IrCC having 36 component codes is used in our system. As a benefit of having the 36-component-IrCC code, the 36-componentIrCC outer code is capable of achieving an improved matching to the EXIT curve of the intrinsically amalgamated inner URC-MPSK coding arrangement.…”
Section: B Near-capacity Channel Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…To approach the capacity, the irregular convolutional code (IrCC) is chosen as it can adjust the shape of its EXIT curve to match that of the SAD-VAMP-SFDE-plus-URCD in turbo equalization. The IrCCs have been widely used in many applications including the near-capacity MMSE turbo equalization [45], [46], cooperative multi-user communications [47], and space-time block code designs [48], [49], etc.…”
Section: B Matching Irregular Recursive Convolutional Codementioning
confidence: 99%
“…We conducted simulations for characterizing the FER performance versus the Signalto-Noise-Ratio (SNR) and followed the approach of [12] for fitting a polynomial to the FER versus SNR curve. The Forward Error Correction (FEC) scheme employed in our paper is an Irregular Convolutional Coded, Unity-Rate Coded and Quadrature Phase-Shift Keying (IrCC-URC-QPSK) [23,24] scheme. The corresponding FER versus SNR curve was generated with the aid of bit-by-bit simulations.…”
Section: A Fer and Power Allocation In A Single-hop Routementioning
confidence: 99%